Never-Part - Histories of Palestine/ Editor: Rasha Salti (3CHOkG, df CaGQb s - Salti, Rasha; Persekian, Jack; Khaldi, Lara (Bozar Expo, 2008)
Exhibition catalog. Editor: Rasha Salti; Curator: Jack Persekian; Assistant: Lara Khaldi; Artists: Jumana Abboud; Tarek Al-Ghoussein; Sobhi al-Zobaidi; Ayreen Anastas; Asad Azi; Mona Hatoum; Janah Hilwe; Emily Jacir; Sliman Mansour; Marwan Rechmaoui; Nida Sinnokrot; Vera Tamari
English; Arabic
Keywords: N4390-5098 Visual Arts. Exhibitions; Palestine (3adSWjfs